الطبيعة المستدامة للوقف الإسلامي - ليلى, جودي; رحماني, موسى (Recherches économiques et managériales, 2018)
هدفت هذه الدراسة إلى معرفة دور الأوقاف الإسلامية في تحقيق التنمية المستدامة ، من خلال إبراز أن الوقف يعد من الركائز الأساسية الداعمة لبرامج التنمية المستدامة، وان الفكر الإسلامي يستوعب كل مقومات التنمية المستدامة ، ما لم تخرج عن مبادئ الإسلام ومقاصده ، حيث ثمة وجهة تقارب بين الفكر الوضعي والإسلامي في مجال التنمية المستدامة . وقد وصلت الدراسة إلى أن للوقف طبيعة مستدامة، تجسدت في ارتباط الوقف بكل من التنمية الاقتصادية فهو فكرة تنموية في حد ذاته، محدث لتراكم الثروة في الاقتصاد، وتركم رأس المال، أما من الناحية الاجتماعية للوقف فقد برزت من خلال قضائه على ظاهرة الفقر و توفير حد الكفاية و القضاء على البطالة، أما بيئيا فان الوقف البيئي يعد إسهاما ماليا لتمويل العمل البيئي، لضمان الموارد للأجيال القادمة . الكلمات المفتاحية : الوقف ، الوقف المستدام ، التنمية المستدامة . Abstract This study aimed at determines the role of Islamic endowments in achieving the sustainable development. Where the researcher believes that the endowment is one of the basic pillars in support of sustainable development programs, and that Islamic thought embraces all ingredients of sustainable development unless they depart from the principles and purposes of Islam. Especially, there is a convergence between positivist and Islamic thought in the field of sustainable development. The study concluded that the endowment has a sustainable nature. This nature is reflected in the connection of the endowment to economic development. It is a development idea in itself, it is updated to accumulate wealth in the economy, It is the accumulation of capital. The endowment is associated with economic development, where endowment eliminates the phenomenon of poverty, it provides a limit for sufficiency, and it eliminates the unemployment. In environment side, the endowment finances the environmental action, for resources continuity to the future generations. Keywords: Endowment, Sustainable Endowment, Sustainable Development .